Improving Adolescent Parenting: Results From a Randomized Controlled Trial of a Home Visiting Program for Young Families. - Jacobs, Francine; Easterbrooks, Ann; Goldberg, Jessica; Mistry, Jayanthi; Bumgarner, Erin; Raskin, Maryna; Fosse, Nathan; Fauth, Rebecca (American Journal of Public Health, 2016)
Objectives. Our aim was to estimate the effects of Healthy Families Massachusetts, a statewide home visiting program serving first-time adolescent parents, on parenting, child development, educational attainment, family planning, and maternal health and well-being. Methods. We used a randomized controlled trial design to randomly assign the 704 participants to a group receiving home visiting services or a control group. Between 2008 and 2012, telephone and in-person interviews were conducted and administrative data obtained at 12 and 24months after enrollment. Intention-to-treat analyses compared group differences across 5 outcome domains: parenting, child health and development, educational and economic achievement, family planning, and parental health and well-being. Results. The home visiting program had a positive influence on parenting stress, college attendance, condom use, intimate partner violence, and engagement in risky behaviors. No negative findings were observed. Conclusions. A paraprofessional home visiting program specifically targeting young mothers appears effective in domains of particular salience to young parents and their infants and toddlers. Expanding participation in the program appears a worthy goal for program administrators and policymakers.